Application Of Digital Technologies For The Manufacturing Of Zirconium Dental Prosthesis Taking Into Account The Individual Parameters Of The Patient's Dentofacial System (Texas Journal of Medical Science, 2025)
The aim of this study is to improve the method for fabricating permanent fixed dental prostheses and implant systems from domestic zirconium dioxide-based materials using a CAD/CAM system. The prosthetic structures were fabricated under dynamic occlusion control using the Hint-Els CAD/CAM system and a virtual articulator. The "Virtual Articulator" software module allowed for the reconstruction, control, and adjustment of the anatomical shape of the structures based on the patient's individual static and dynamic occlusal parameters. Milling strategy parameters were also optimized by calculating milling paths and reducing the overall fabrication time, while maintaining high accuracy, as confirmed by a comparator microscope study. Evaluation of regional periodontal blood flow late after orthopedic treatment indicates normalization of periodontal tissue microcirculation in the functional aspect due to adjusted occlusal contacts